The Influence of Information Technology Based Audit Procedures and Audit Experience on Audit Quality - Neni Maryani; Rendi Kusuma Natita; Ali Rahman Reza Zaputra (International Journal of Quantitative Research and Modeling, 2023)
The Ministry of Finance as one of the regulators in Indonesia has also issued regulation Number 186 /PMK.01/2021 concerning the Development and Supervision of Public Accountants which is effective on March 15 2022 (Janah et al., 2022). This regulation did not appear without reason. Several cases related to audited financial statements have occurred in recent years. Some of the financial reports that are cases include the financial reports of PT. Garuda Indonesia Tbk which was audited by the Public Accounting Firm Tanubrata Sutanto Fahmi Bambang and Partners which is also an international affiliated Public Accounting Firm, namely BDO International, where the financial reports of PT (Setiono et al., 2020).